Resin pellet composition, its manufacturing method, and microporous membrane manufacturing method

The resin pellet composition with a porous polyolefin structure impregnated by a liquid component addresses classification, kneading, and transportability issues, ensuring uniform dispersion and clog-free transport for high-quality microporous membranes.

JP7610775B2Active Publication Date: 2025-01-09ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023511520
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-30
Publication Date
2025-01-09
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

Conventional resin pellets exhibit poor classification properties when mixed with materials of different particle sizes, difficulty in uniformly dispersing with liquid components during kneading, and poor transportability due to low bulk density and potential for piping clogs during pneumatic transportation.

Method used

A resin pellet composition comprising polyolefin pellets with a porous structure impregnated by a liquid component, ranging from 0.1% to 99.0% by mass, which maintains porosity and absorbs liquid components, enhancing kneading properties and transportability while reducing classification issues.

Benefits of technology

The composition achieves improved kneading uniformity with liquid components, reduces classification, and ensures efficient pneumatic transport without clogging, resulting in high-quality microporous membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610775000006
    Figure 0007610775000006
  • Figure 0007610775000007
    Figure 0007610775000007
  • Figure 0007610775000008
    Figure 0007610775000008
Patent Text Reader

Abstract

The present invention provides: a resin pellet composition excellent in terms of low-classification property, kneadability with liquid ingredients, and transportability; a method for producing the resin pellet composition; and a method for producing a microporous polyolefin film from the resin pellet composition. The resin pellet composition comprises first pellets, which comprise a polyolefin, and 0.1-99.0 mass% liquid component. The first pellets are porous objects, some of which contain some of the liquid component infiltrated thereinto. In another embodiment, the resin pellet composition includes second pellets, which include a polyolefin. The second pellets are non-porous objects each comprising a portion made of a resin comprising the polyolefin and a portion made of a liquid component. The mass of the liquid component present on the outer surfaces of the second pellets is 20 mass% or less with respect to the total mass of the second pellets.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin pellet composition and a method for producing the same, and a method for producing a microporous membrane. [Background technology]

[0002] Polyolefin resins such as polyethylene and polypropylene have a good balance of molded product properties, moldability, weather resistance, etc., and are widely used in the production of industrial films such as packaging films and agricultural films, blow molding applications such as bottle containers, injection molding applications such as structural materials and large containers, fiber applications such as monofilaments, etc. Recently, they have also been used in the production of microporous membranes as separators for lithium ion batteries.

[0003] A common method for obtaining pellets of a polyolefin resin composition is the method described in Patent Document 1, that is, a method in which polymerized polyethylene powder is heated and kneaded in an extruder to form pellets. For example, the polyolefin resin is extruded into strands having a diameter of 10 mm or less, generally about 1 to 5 mm, and the extrusion product is cut in the longitudinal direction to about 2 to 5 mm to obtain pellets.

[0004] On the other hand, a method is also known in which a resin composition is once molded into a film or the like and then repelletized. For example, Patent Document 2 describes a method in which a part of the obtained resin film is compressed without being heated, and then cut into a desired length to obtain resin pellets.

[0005] Patent Document 3 also describes resin pellets containing polyethylene as a main component, which can be obtained from a resin film. The resin pellets are described as being in a folded, separable or laminated form in a first embodiment, and as being in a planar, fibrous, hollow fiber or nonwoven fabric form in a second embodiment. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-101854 [Patent Document 2] JP 2006-21519 A [Patent Document 3] JP 2019-142002 A [Patent Document 4] JP 2007-23171 A [Patent Document 5] International Publication No. 2005 / 103127 [Patent Document 6] International Publication No. 2006 / 38532 [Patent Document 7] Special Publication No. 6-15721 [Patent Document 8] Patent No. 4623780 Summary of the Invention [Problem to be solved by the invention]

[0007] In order to impart desired properties to molded products, resin pellets may be mixed with materials (mixtures) having different particle sizes, such as other resin pellets or powders. Therefore, resin pellets are required to be difficult to classify when mixed with mixtures (low classification ability). In addition, for example, in the production of microporous membranes by a wet method, resin pellets may be kneaded with liquid components. Therefore, resin pellets are required to disperse the liquid components more uniformly when kneaded with the liquid components in an extruder (kneadability). Furthermore, in the manufacturing process of molded products, resin pellets are often transported via air transport such as an empty line. Therefore, during air transport, it is required to be easy to transport without causing clogging of piping (transportability).

[0008] However, conventional pellets such as those described in Patent Documents 1 to 3 tend to be classified when mixed with other materials having different particle sizes, particularly resin powder. In addition, when the pellets having the general shape described in Patent Document 1 are kneaded with liquid components in an extruder, the liquid components may not be uniformly dispersed, which may impair the quality of the resulting film such as a microporous membrane. In addition, pellets having a film-like structure such as those described in Patent Documents 2 and 3 have a low bulk density, so there is a concern that they may not be transported well by air transport or may cause clogging of pipes. Therefore, conventional pellets such as those described in Patent Documents 1 to 3 have room for improvement in the low classification of pellets, kneadability with liquid components, and transportability.

[0009] An object of the present disclosure is to provide a resin pellet composition that is excellent in transportability and kneadability with a liquid component, a method for producing the same, and a method for producing a polyolefin microporous membrane using the resin pellet composition. [Means for solving the problem]

[0010] Examples of embodiments of the present disclosure are listed below. [1] First pellets comprising a polyolefin; A resin pellet composition containing 0.1% by mass or more and 99.0% by mass or less of a liquid component, The resin pellet composition, wherein the first pellet is a porous body, and a portion of the porous body is impregnated with a portion of the liquid component. [2] 2. The resin pellet composition according to item 1, wherein the porous body of the first pellet has a microporous membrane-like component and / or a bundle, knit, woven fabric or nonwoven fabric-like component made of fibers or hollow fibers. [3] The porous body of the first pellet includes a microporous membrane-like component having a thickness of 50 μm or less and having fibrils having a diameter of 1 μm or less, and / or Item 3. The resin pellet composition according to item 2, wherein the porous body of the first pellet is a bundle, knit, woven or nonwoven fabric made of fibers or hollow fibers, and includes a component part having a fiber diameter of 500 μm or less. [4] 4. The resin pellet composition according to any one of items 1 to 3, wherein the amount of the liquid component contained in the first pellets is 0.1% by mass or more and 50.0% by mass or less based on the total mass of the resin pellet composition. [5] The liquid component is a plasticizer, the viscosity average molecular weight of the polyolefin contained in the first pellets or the viscosity average molecular weight of the entire resin constituting the first pellets is 200,000 or more; 5. The resin pellet composition according to any one of items 1 to 4, wherein the first pellet is in a folded, separable, or stacked form. [6] 6. The resin pellet composition according to any one of items 1 to 5, wherein the first pellets can further contain 5% by mass or more of a liquid component in addition to the liquid component. [7] 7. The resin pellet composition according to any one of items 1 to 6, wherein the mass of the liquid component present on the outer surface of the first pellet is 20 mass% or less based on the total mass of the first pellet, and the mass of the liquid component present on the outer surface is measured by the following method. 20 g of the first pellet is collected. 20 g of the first pellet is wrapped in a square sheet with a side of 1 m and a thickness of 0.6 mm, which is made of multiple layers of polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the liquid component present on the outer surface of the pellet is wiped off. When the liquid component transfers to the sheet, the color of that part changes to translucent. The sheet is replaced and the wiping operation is repeated multiple times until the color change of the sheet can no longer be confirmed. Thereafter, the mass of the first pellet is measured, and the difference in mass before and after the wiping operation is taken as the amount of liquid component present on the outer surface of the first pellet. [8] 8. The resin pellet composition according to any one of items 1 to 7, wherein the mass of the liquid component present inside the first pellet is 0 mass% or more and 70 mass% or less with respect to the total mass of the first pellet, and the mass of the liquid component present inside the first pellet is measured by the following method. 20 g of the first pellets are collected. 20 g of the first pellets are wrapped in a square sheet with a side length of 1 m and a thickness of 0.6 mm, which is made by stacking multiple polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the liquid components present on the outer surface of the pellets are wiped off. When the liquid components transfer to the sheet, the color of that part changes to translucent. The sheet is replaced and the wiping operation is repeated multiple times until the color change of the sheet can no longer be confirmed. Thereafter, when the liquid components are extracted and removed from the first pellets with a solvent, the mass difference before and after extraction is taken as the mass of the liquid components present inside the first pellets. [9] a resin pellet composition comprising a second pellet comprising a polyolefin; the second pellet is a non-porous body having a portion made of the polyolefin-containing resin and a portion made of the liquid component, A resin pellet composition, wherein the mass of the liquid component present on the outer surface of the second pellet is 10 mass% or less relative to the total mass of the second pellet, and the mass of the liquid component present on the outer surface is measured by the following method. 20 g of the second pellet is collected. 20 g of the second pellet is wrapped in a square sheet with a side of 1 m and a thickness of 0.6 mm, which is made of multiple layers of polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the liquid component present on the outer surface of the pellet is wiped off. When the liquid component transfers to the sheet, the color of that part changes to translucent. The sheet is replaced and the wiping operation is repeated multiple times until the color change of the sheet can no longer be confirmed. Thereafter, the mass of the second pellet is measured, and the difference in mass before and after the wiping operation is taken as the amount of liquid component present on the outer surface of the second pellet.

[10] 10. The resin pellet composition according to item 9, wherein the second pellet has an angle of repose of less than 60 degrees.

[11] Item 11. The resin pellet composition according to item 9 or 10, wherein a mass of the liquid component present inside the second pellet is 30 mass% or more based on a total mass of the second pellet, and the mass of the liquid component present inside the second pellet is measured by the following method. 20 g of the second pellets are collected. 20 g of the second pellets are wrapped in a square sheet with a side length of 1 m and a thickness of 0.6 mm, which is made of multiple layers of polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the liquid components present on the outer surface of the pellets are wiped off. When the liquid components transfer to the sheet, the color of that part changes to translucent. The sheet is replaced and the wiping operation is repeated multiple times until the color change of the sheet can no longer be confirmed. Thereafter, the difference in mass before and after extraction when the liquid components are extracted and removed from the first pellets with a solvent is taken as the mass of the liquid components present inside the first pellets.

[12] further comprising a second pellet comprising a polyolefin; 9. The resin pellet composition according to any one of items 1 to 8, wherein the second pellets are non-porous and have a portion made of the resin containing the polyolefin and a portion made of the liquid component.

[13] Item 13. The resin pellet composition according to item 12, wherein a mass ratio of the first pellets to the second pellets (first pellets / second pellets) is 10 / 90 to 90 / 10.

[14] Item 14. The resin pellet composition according to item 12 or 13, wherein the porosity after the liquid component is extracted from the first pellets is more than 10% and not more than 90%.

[15] 15. The resin pellet composition according to any one of items 12 to 14, wherein the first pellets and / or the second pellets contain polyethylene having a viscosity average molecular weight of 200,000 or more.

[16] 16. The resin pellet composition according to any one of items 12 to 15, wherein the first pellets and / or the second pellets are made of recycled resin.

[17] 17. The resin pellet composition according to any one of items 12 to 16, wherein the amount of the liquid component contained in the second pellets is 20% by mass or more and 90% by mass or less based on the total mass of the resin pellet composition.

[18] 18. The resin pellet composition according to any one of items 12 to 17, wherein the first pellets and / or the second pellets have an angle of repose of less than 60 degrees.

[19] 19. A method for producing a microporous polyolefin membrane, comprising extruding and stretching the resin pellet composition according to any one of items 1 to 18, and extracting the liquid component with a solvent to open pores.

[20] A method for producing a resin pellet composition according to any one of items 12 to 18, comprising: an extrusion step of extruding a composition containing a polyolefin-containing resin and a liquid component with an extruder to form a raw microporous membrane; an extraction step of extracting the liquid component from the raw microporous membrane in the presence of an extraction solvent; Including, The method for producing a resin pellet composition further includes obtaining a second pellet raw material from the microporous membrane raw material before the extraction step after the extrusion step, obtaining a first pellet raw material from the microporous membrane raw material after the extraction step, and mixing the first pellet raw material and the second pellet raw material. [twenty one] A method for producing a resin pellet composition according to any one of items 12 to 18, comprising: a first pellet raw material production step including a first extrusion step of extruding a composition containing a polyolefin-containing resin and a liquid component with an extruder to form a raw microporous membrane; an extraction step of extracting the liquid component from the raw microporous membrane obtained in the first extrusion step in the presence of an extraction solvent; and obtaining a first pellet raw material from the raw microporous membrane after the extraction step; a second extrusion step of extruding a composition containing a polyolefin-containing resin and a liquid component with an extruder to form a raw microporous membrane, and a second pellet raw material production step of obtaining a second pellet raw material from the raw microporous membrane obtained in the second extrusion step; and A step of mixing the first pellet raw material and the second pellet raw material. The present invention further provides a method for producing a resin pellet composition. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide a resin pellet composition that is excellent in low classification properties, kneadability with liquid components, and transportability. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1(a) is a schematic oblique view of a resin pellet having a planar film laminated thereon, FIG. 1(b) is a schematic cross-sectional view of FIG. 1(a), FIG. 1(c) is a schematic cross-sectional view of a resin pellet having a folded planar film, and FIG. 1(d) is a schematic cross-sectional view of a resin pellet having a rolled or folded planar film. [Diagram 2] FIG. 2(a) is a schematic perspective view of a resin pellet on which a planar film has been laminated and which has been embossed, and FIG. 2(b) is a schematic cross-sectional view of FIG. 2(a). [Diagram 3] 3(a) and (b) are schematic diagrams showing an example of a production line for resin pellets. [Figure 4] FIG. 4 is a schematic diagram showing an example of the shape of the second pellets and the raw material thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Resin pellet composition> <First Pellet> The resin pellet composition of the present disclosure includes a first pellet (also referred to as a "porous pellet") containing polyolefin and 0.1% by mass or more and 99.0% by mass or less of a liquid component. The first pellet is a porous body, and a part of the first pellet is impregnated with a part of the liquid component. Since the resin pellet composition contains a liquid component in advance, the liquid component binds the materials of the resin pellet composition together, and classification is less likely to occur. In addition, even when the resin pellet composition is mixed with other materials having different particle sizes, such as resin powder, as necessary, the presence of the liquid component can reduce classification while suppressing the generation of dust due to the resin powder. In addition, since a part of the liquid component is impregnated into a part of the porous body of the first pellet, the resin is swelled by the liquid component in advance, and when the resin pellet composition is kneaded, the resin pellet and the liquid component can be kneaded more uniformly. In addition, even if the resin pellet composition contains a liquid component in advance, the first pellet, which is a porous body, absorbs a part of the liquid component, so that the stickiness of the resin pellet composition can be suppressed. Furthermore, since the first pellet is a porous body, the bulk density is lower than that of a non-porous body, and the porous body absorbs a part of the liquid component, so that the porous body becomes moderately heavy and has excellent transportability. The porous body refers to a material having a large number of pores. The porous body may have a large number of pores with a pore diameter of 10 nm to 100 nm, a porosity of about 20% to 70%, and a puncture strength of about 100 gf to 1000 gf. The porous body may be, for example, a microporous membrane obtained by the method described in Patent Document 5 or Patent Document 6, and may be, for example, a microporous membrane used in a separator for a lithium ion secondary battery. The porous body may be a multi-layered microporous membrane. The non-porous body is a material that is not a porous body. The non-porous body may be, for example, a material that does not substantially have pores, or a material in which the pores are impregnated with another material, for example, a liquid component, and is non-porous as a whole. As long as the non-porous body is a material that is non-porous as a whole, a part of it, for example, its surface, may have a porous portion. The distinction between porous and non-porous bodies can be made by observation using a SEM or the like.

[0014] The first pellets are pellets containing a polyolefin and are porous bodies. A part of the porous body of the first pellets is impregnated with a part of the liquid component contained in the resin pellet composition.

[0015] The liquid component does not impregnate the entire porous body of the first pellet, and the first pellet maintains at least a part of its porosity. As long as the first pellet maintains at least a part of its porosity, a part of the porous body may be pressed, bonded or fused to form a non-porous part, as described below.

[0016] In this specification, the term "resin pellets" refers to particulate lumps of resin having a size suitable for use as a raw material in conventional extrusion molding processes, such as film molding such as inflation molding, microporous membrane molding, hollow fiber molding, blow molding, injection molding, pipe molding, monofilament molding, and the like.

[0017] The amount of the first pellets in the resin pellet composition is preferably 10% by mass or more and 95% by mass or less, more preferably 15% by mass or more and 80% by mass or less, and even more preferably 30% by mass or more and 70% by mass or less, based on the total mass of the resin pellet composition, from the viewpoints of low classification of the resin pellet composition, kneadability with liquid components, and transportability.

[0018] The amount of the liquid component contained in the first pellet is preferably more than 0.1% by mass and not more than 50.0% by mass, more preferably 0.1% by mass or more and not more than 30% by mass, even more preferably 0.5% by mass or more and not more than 10% by mass, still more preferably 0.5% by mass or more and not more than 10% by mass, still more preferably 0.5% by mass or more and not more than 5% by mass, and particularly preferably 1.0% by mass or more and not more than 5% by mass, based on the total mass of the resin pellet composition. When the amount of the liquid component contained in the first pellet is within these ranges, the low classification property of the resin pellet composition, the kneadability with the liquid component, and the transportability tend to be further improved.

[0019] A part of the liquid component contained in the first pellet may be present on the outer surface of the first pellet. When the resin pellet composition further contains a second pellet, a part or all of the liquid component contained in the first pellet may be present on the outer surface of the first pellet. The upper limit of the mass of the liquid component present on the outer surface of the first pellet is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 2% by mass or less, based on the total mass of the first pellet. The lower limit that can be combined with these upper limits is not particularly limited, but can be preferably 0% by mass or more, more than 0% by mass, 0.1% by mass or more, 0.2% by mass or more, or 1% by mass or more. When the amount of the liquid component present on the outer surface of the first pellet is within these ranges, the kneadability and transportability of the resin pellet composition with the liquid component are further improved, and the bridging in the hopper of the extruder is also improved, so that extrusion fluctuations can be further suppressed.

[0020] The mass of the liquid component present on the outer surface of the first pellet is measured by the following method. First, 20 g of the first pellet is collected. The liquid component present on the outer surface of the first pellet is wiped off with a sheet of 1 m square and 0.6 mm thick, which is made of multiple layers of polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm. When the liquid component transfers to the sheet, the color of that part changes to translucent. This wiping operation is repeated several times by replacing the sheet until the liquid component does not soak into the sheet, that is, until the color change of the sheet cannot be confirmed. Thereafter, the mass of the first pellet is measured, and the mass difference before and after the wiping operation is taken as the amount of the liquid component present on the outer surface of the first pellet. A more detailed measurement method will be described in the Examples.

[0021] A part of the liquid component contained in the first pellet may be present inside the first pellet. The lower limit of the mass of the liquid component present inside the first pellet can be preferably 0% by mass or more, more than 0% by mass, 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 5% by mass or more, 10% by mass or more, 20% by mass or more, or 50% by mass or more, based on the mass of the entire first pellet. The upper limit that can be combined with these lower limits is not particularly limited, but can be preferably 70% by mass or less, 65% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 10% by mass or less, or 5% by mass or less. When the amount of the liquid component present inside the first pellet is within these ranges, the kneadability and transportability of the resin pellet composition with the liquid component are further improved, and extrusion fluctuations can be further suppressed. For example, in the production of a microporous membrane used as a separator for a lithium ion secondary battery, the mass of the liquid component present inside the first pellet is preferably 0 mass % or more and 5 mass % or less.

[0022] The mass of the liquid component present inside the first pellet is measured by the following method. First, 20 g of the first pellet is collected. The liquid component present on the outer surface of the first pellet is wiped off with a sheet of 1 m square and 0.6 mm thick, which is made of multiple layers of polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm. When the liquid component transfers to the sheet, the color of that part changes to translucent. This wiping operation is repeated multiple times by replacing the sheet until the liquid component does not soak into the sheet, that is, until the color change of the sheet cannot be confirmed. Thereafter, when the liquid component is extracted and removed from the first pellet with a solvent, the mass difference before and after the extraction is taken as the mass of the liquid component present inside the first pellet. A more detailed measurement method will be described in the Examples.

[0023] The upper limit of the angle of repose of the first pellets is preferably less than 60 degrees, more preferably less than 50 degrees, and even more preferably less than 45 degrees. The lower limit that can be combined with these upper limits is not particularly limited, but can be preferably 20 degrees or more, 15 degrees or more, or 10 degrees or more. By having the angle of repose of the first pellets within the above range, the kneadability with the liquid component of the resin pellet composition and the transportability are further improved, and further classification is suppressed when the pellet composition of the present invention is dry-blended with other general pellets, such as polypropylene pellets, and extrusion fluctuations can be further suppressed.

[0024] The first pellets have a porosity of preferably 5% to 95%, more preferably 10% to 80%, even more preferably 20% to 60%, and even more preferably 30% to 50% after the liquid component is extracted. If the porosity of the first pellets after the liquid component is extracted is within these ranges, the resin pellet composition tends to have improved low classification properties, kneadability with the liquid component, and transportability.

[0025] Regarding the dimensions of the first pellets, the maximum length of the first pellets is preferably 10 mm or less from the viewpoint of being less likely to clog during air transport in an empty line or the like and being easy to transport, and more preferably 6 mm or less, and even more preferably 5 mm or less, from the viewpoint of further improving transportability in the extruder. The lower limit of the maximum length is preferably 1 mm or more, more preferably 2 mm or more. The maximum length of the first pellets is preferably 1 mm or more, in order to transport the resin pellet composition well, particularly in a large extruder with a large clearance between the screw and the cylinder. The "maximum length" of the pellets is, for example, the longest diameter in the case of an oval sphere, the maximum diagonal length in the case of a rectangular parallelepiped, and the length in the case of fibers, and the maximum projected length is used in the case of other shapes as well.

[0026] The first pellets are preferably resin pellets containing polyolefin as a main component. In this specification, the term "main component" means that the first pellets contain polyolefin in a proportion of more than 50% by mass based on the total mass of all resin components. Examples of polyolefin include polyethylene and polypropylene, and polyethylene is preferred.

[0027] The main component of the first pellets is preferably melt-kneaded polyethylene. It is known in the art that the strength of a polymer molded article varies depending on the number of entanglement points between tie molecules. Without wishing to be bound by theory, it is believed that melt-kneading reduces the crystallite size of the polymer and increases the number of entanglement points between tie molecules, thereby improving the strength of the resin pellets and molded articles using the same. The melt-kneading of polyethylene can be carried out using a melter and / or kneader, or a general twin-screw extruder or single-screw extruder.

[0028] The first pellet may contain polypropylene or other polyolefin resins in addition to polyethylene to improve heat resistance. In addition to polyolefin, the first pellet may contain other resins, such as polyethylene terephthalate (PET) and non-polyolefin resins such as nylon, within a range that does not impair the performance of the resin pellet composition of the present disclosure. When the first pellet is a mixture of polyethylene and a resin other than polyethylene, the ratio of the resin other than polyethylene in the pellet is preferably less than 30% by mass from the viewpoint of dispersibility and / or strength retention, more preferably less than 20% by mass, and even more preferably less than 10% by mass from the viewpoint of dispersibility. The lower limit is not particularly limited, but can be, for example, 0% by mass or more, or more than 0% by mass.

[0029] The viscosity average molecular weight (Mv) of the polyolefin contained in the first pellet (porous pellet) or the entire resin constituting the first pellet is preferably 200,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. When the Mv of the polyethylene contained in the first pellet or the entire resin constituting the first pellet is 200,000 or more, when the resin pellet is mixed with a resin containing a low molecular weight component with Mv less than 200,000 as a main component, the mechanical strength of the molded product or film of the mixture, such as tear strength and tensile strength, is significantly improved, which is particularly advantageous for applications requiring mechanical strength such as microporous membranes. The upper limit of the Mv is not particularly limited, but can be, for example, 5,000,000 or less, preferably 3,000,000 or less, and more preferably 2,000,000 or less.

[0030] From the viewpoint of tensile strength of the molded article, the Mv of the polyethylene contained in the first pellets is preferably more than 200,000, more preferably 300,000 or more (or more), and even more preferably 500,000 or more (or more). From the same viewpoint, the Mv of the first pellets is preferably 300,000 or more, more preferably 500,000 or more. The upper limit of the Mv is not particularly limited, but can be, for example, 5,000,000 or less, preferably 3,000,000 or less, and even more preferably 2,000,000 or less.

[0031] The polyethylene in the first pellets may be a mixture of components having different molecular weights, for example, a mixture of polyethylene with Mv 100,000 and polyethylene with Mv 700,000 may have an overall Mv of 200,000 or more.

[0032] The first pellets are preferably made of recycled resin from the viewpoints of productivity, environmental consideration, etc. In the present specification, "recycled resin" means a product such as a film, a blown container, an injection molded product, or an intermediate product before the product, a product not conforming to the standard, etc., and is pelletized from a resin molded product that has been subjected to at least one melting, kneading, and extrusion process. For example, as described later, it is more preferable that the raw material of the first pellets is formed from a polyolefin microporous membrane raw roll after the extraction process. Even when the first pellets are made of recycled resin, the viscosity average molecular weight (Mv) of the polyethylene is preferably 200,000 or more (or more), more preferably 300,000 or more (or more), and even more preferably 500,000 or more (or more) from the viewpoint of the strength of a molded product using the resin pellets. The upper limit of the Mv is not particularly limited, but can be, for example, 1,000,000 or less.

[0033] Examples of polyethylene include high density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMWPE), linear low density polyethylene (LLDPE), high pressure low density polyethylene, and mixtures thereof. In addition, polyethylene with a narrow molecular weight distribution obtained by utilizing a metallocene catalyst and HDPE obtained by multi-stage polymerization may be used. In this specification, ultra-high molecular weight polyethylene (UHMWPE) refers to polyethylene with a viscosity average molecular weight (Mv) of 350,000 or more.

[0034] When the first pellets contain polyethylene, the proportion of polyethylene is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total mass of the resin components of the first pellets. When the first pellets contain UHMWPE, the proportion of UHMWPE is preferably 5% by mass or more and 50% by mass or less from the viewpoints of optical properties, strength, and foreign matter removability of the molded product, and is preferably 9% by mass or more and 40% by mass or less from the viewpoint of dispersibility, based on the total mass of the resin components of the first pellets.

[0035] The first pellets are preferably planar, folded (folded form), separable (separable form), or laminated (laminated form). By having one or more of these forms, resin pellets having excellent strength and optical properties during film formation and excellent removal of foreign matter such as fish eyes and unmelted gels can be obtained. This is because the pellets efficiently transmit shear force in the extruder and can be kneaded to uniformly stretch the molecular chains of polyethylene contained in the pellets, thereby reducing foreign matter such as fish eyes and unmelted gels. The first pellets are more preferably in a folded form, separable form, or laminated form. This is because, in addition to reducing the foreign matter, the first pellets are more likely to retain liquid components, resulting in a resin pellet composition having excellent transportability, low classification properties, and kneadability with liquid components.

[0036] FIG. 1(a) shows a schematic perspective view of a resin pellet having a laminated form of a planar film. The cross section of the laminated resin pellet can have, for example, individual planes (FIG. 1(b)). The cross section of the folded resin pellet can have, for example, one ends of a plurality of planar components bonded together (FIG. 1(c)). As shown in FIG. 1(d), the resin pellet may have a cross section in which a planar microporous film is rolled or folded. Since FIGS. 1(a) to (d) are schematic, the resin pellet of the present disclosure is not limited to one having a regular laminated form as shown in FIGS. 1(a) to (d).

[0037] The resin pellets in the separable form may be connected to such an extent that at least a part of the pellets maintains the shape of the pellets when transported by air transport (without impairing transportability) and can be separated by applying force by hand. The resin pellets in the separable form may specifically have a non-bonded part, and more specifically may have a non-compressed part, a non-adhesive part, or a non-fused part. For example, as shown in FIG. 2(a), a resin pellet having both a bonded part and a non-bonded part (FIG. 2(b)) is obtained by embossing a pellet having a folded or laminated form as shown in FIG. 2(a) and (b) are schematic, and therefore the resin pellets of the present disclosure are not limited to those having the regular laminated form and embossed part shown in FIG. 2(a) and (b).

[0038] The porous body of the first pellet preferably includes a microporous membrane-like component, a bundle, knitted fabric, woven fabric or nonwoven fabric-like component made of fibers or hollow fibers, or a combination thereof. By including at least one of these components, the porous body can easily absorb liquid components into a part of the porous body, and therefore a resin pellet composition having excellent transportability, low classification ability, and kneadability with liquid components can be obtained.

[0039] When the porous body of the first pellet has a microporous membrane-like portion, the thickness of one microporous membrane-like portion is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The microporous membrane-like portion preferably has fibrils with a diameter of 10 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less. When the porous body of the first pellet has a bundle, knit, woven fabric, or nonwoven fabric-like portion made of fibers or hollow fibers, the fiber diameter is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. When the first pellet has such a portion, the molecular chains of the polyolefin contained in the pellet can be uniformly stretched to ensure strength and foreign matter removal when forming a microporous membrane from the pellet and other materials. By having a film thickness or fiber diameter of 100 μm or less, it is not necessary to reduce the extrusion rate in order to reduce unmelted gels. When the film thickness or fiber diameter is 50 μm or less, the resin is already dispersed to 50 μm or less, so that even if a high molecular weight component is contained, unmelted gels are hardly or not observed visually. This is thought to be because the dimensions are smaller than those of general polyethylene powders, and the crystalline region of the polyethylene is also stretched to a level of 50 μm, so that good dispersion is obtained even when melt-kneaded with LLDPE. The smaller the film thickness or fiber diameter, the better the dispersion. The lower limit of the film thickness or fiber diameter is not limited, but it is preferably 1 μm or more, 3 μm or more, or 4 μm or more from the viewpoint of handleability.

[0040] It is particularly preferred that the first pellets have a viscosity average molecular weight (Mv) of 200,000 or more for the polyethylene contained therein or for the entire resin constituting the first pellets, and have a thin film structure as described above. The technical background and significance of this will be explained below. In recent years, molded and processed products such as microporous membranes and films have become thinner from the viewpoint of saving raw materials used, but it has become necessary to prevent a decrease in mechanical strength associated with the thinner membrane. In order to improve membrane strength, a technique has been proposed in the past that uses a high molecular weight component as a resin raw material. For example, Patent Document 4 describes a polyethylene resin composition with an extremely high molecular weight. However, this has too high a viscosity when used alone, and in extrusion molding such as a general inflation method, the resin pressure or load current of the molding machine becomes too high to form a film. Therefore, there is a method in which such a polyethylene resin composition having a very high molecular weight is mixed in the form of a resin powder with conventional linear low density polyethylene (LLDPE) or low density polyethylene (LDPE) resin pellets and kneaded in an extruder. However, kneading is insufficient, and the strength does not increase, and the high molecular weight component remains in the film as so-called fish eyes or unmelted gel, which is a phenomenon presumed to be caused by poor dispersion of the high molecular weight component. These phenomena are particularly likely to occur when a polyolefin composition with a high molecular weight, generally a polyolefin composition with a viscosity average molecular weight of more than about 200,000, is used. It is presumed that the cause is that the low molecular weight component softens first in the extruder, but sufficient shear stress necessary for dispersion is not transmitted to the high molecular weight component that softens slowly. That is, it is presumed that the molecular chains of such high molecular weight components are very long, so that the energy that can be provided to disentangle the crystals inside a general extruder is insufficient, and the molecular chains remain in an undisentangled state. In addition, the powder of the high molecular weight component generally has a high viscosity and takes a long time to knead, which is also considered to be a factor of poor dispersion in the extruder. In contrast, in a preferred embodiment of the present disclosure, by using a first pellet having a shape such as a thin film, the resin component can be efficiently melted in the extruder and the molecular chains can be sufficiently disentangled by applying a shear force. Even if the viscosity average molecular weight (Mv) is 200,000 or more, poor dispersion rarely occurs. Therefore, the mechanical strength of the molded product can be increased by reducing the amount of the conventional high molecular weight resin powder to be mixed, or without mixing it at all. Therefore, poor dispersion and classification of materials caused by the conventional high molecular weight resin powder can be reduced or avoided.

[0041] The first pellets can preferably contain 5% by mass or more of the liquid component in addition to the liquid component already contained therein, more preferably 10% by mass or more of the liquid component, and particularly preferably 20% by mass or more. The above means that the first pellets have the property of absorbing the liquid component in addition to the liquid component already contained therein, and for example, the property can be evaluated from the mass change before and after exposing the pellets to an excess amount of the liquid component. The measurement method is described in the examples. The upper limit of the amount of the liquid component that can be further contained is not particularly limited, but may be, for example, 65% by mass or less, preferably 60% by mass or less, and more preferably 50% by mass or less. When the liquid component can be further contained within the above range, the stickiness of the pellets is further suppressed, and the transportability and extrusion properties are further improved.

[0042] The first pellet has a bulk density of 0.1 g / cm3 after the liquid component is extracted, as measured according to the Japan Powder Industry and Technology Association standard SAP01-79. 3 ~0.4g / cm 3 By having a bulk density in this range, a resin pellet composition can be obtained that is excellent in strength and optical properties when formed into a film, and is also excellent in the removal of foreign matter such as fish eyes and unmelted gels. The bulk density of the first pellets is preferably 0.35 g / cm from the viewpoint of further improving the strength, optical properties, or foreign matter removal properties of a film obtained by using the first pellets. 3 less than 0.30 g / cm 3 More preferably, 0.28 g / cm 3 is less than.

[0043] <Second Pellet> The resin pellet composition further contains a second pellet (also referred to as a "non-porous pellet") containing polyolefin, and the second pellet is preferably a non-porous body having a portion consisting of a resin containing polyolefin and a portion consisting of a liquid component. The non-porous body may have a porous portion in a part thereof, for example, on its surface, as long as it is a non-porous material as a whole. The non-porous body may be, for example, a mixture in which a resin and a liquid component are generally melt-kneaded and the liquid component is not extracted and removed. By containing a second pellet having a portion consisting of a liquid component in addition to the first pellet, the amount of liquid component contained in the entire resin pellet composition can be increased. Therefore, the time for swelling the resin pellet composition with the liquid component during extrusion can be greatly shortened, and the kneadability with the liquid component is further improved. As a result, the removability of fish eyes, unmelted gels, etc. is excellent. In addition, even if the amount of liquid component contained in the entire resin pellet composition increases, the first pellet, which is a porous body, absorbs a part of the liquid component, so that the stickiness of the resin pellet composition can be suppressed. Furthermore, since the second pellets are non-porous, the bulk density of the entire resin pellet composition can be increased, and transportability can be further improved. The second pellets are preferably a melt-kneaded mixture of a polyolefin-containing resin and a liquid component, and may be porous when the liquid component is extracted from the second pellets.

[0044] The amount of the second pellets in the resin pellet composition is preferably 10% by mass or more and 90% by mass or less based on the total mass of the resin pellet composition, from the viewpoints of the low classification property of the resin pellet composition, the kneading property with the liquid component, and the transportability. The mass ratio of the first pellets to the second pellets (first pellets / second pellets) is preferably 10 / 90 to 90 / 10, more preferably 20 to 80, and further preferably 30 to 60, from the viewpoints of the low classification property of the resin pellet composition, the kneading property with the liquid component, and the transportability.

[0045] The amount of the liquid component contained in the second pellets is preferably 10% by mass or more and 90% by mass or less, more preferably 20% by mass or more and 90% by mass or less, even more preferably 30% by mass or more and 80% by mass or less, and even more preferably 40% by mass or more and 70% by mass or less, based on the total mass of the resin pellet composition. When the amount of the liquid component contained in the second pellets is within these ranges, the low classification property of the resin pellet composition, the kneadability with the liquid component, and the transportability tend to be further improved.

[0046] A part of the liquid component contained in the second pellet may be present on the outer surface of the second pellet. The upper limit of the mass of the liquid component present on the outer surface of the second pellet is preferably 10% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less, based on the total mass of the second pellet. The lower limit that can be combined with these upper limits is not particularly limited, but can be preferably 0% by mass or more, more than 0% by mass, 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more. When the amount of the liquid component present on the outer surface of the second pellet is within these ranges, the kneadability with the liquid component of the resin pellet composition and the transportability are further improved, and there is no adhesion between the pellets, and extrusion fluctuations can be further suppressed.

[0047] The mass of the liquid component present on the outer surface of the second pellet is measured according to the method for measuring the mass of the liquid component present on the outer surface of the first pellet described above. More detailed measurement methods are described in the Examples.

[0048] A part or all of the liquid component contained in the second pellet may be present inside the second pellet. The lower limit of the mass of the liquid component present inside the second pellet is preferably 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, or 50% by mass or more, based on the mass of the entire second pellet. The upper limit that can be combined with these lower limits is not particularly limited, but can be preferably 70% by mass or less, 65% by mass or less, or 60% by mass or less. When the amount of the liquid component present inside the second pellet is within these ranges, the kneadability with the liquid component of the resin pellet composition and the transportability are further improved, and extrusion fluctuations can be further suppressed. In addition, there is no bleeding out after storage over time.

[0049] The mass of the liquid component present inside the second pellets is measured according to the method for measuring the mass of the liquid component present inside the first pellets described above. More detailed measurement methods are described in the Examples.

[0050] The upper limit of the angle of repose of the second pellets is preferably less than 60 degrees, more preferably less than 50 degrees, and even more preferably less than 45 degrees. The lower limit that can be combined with these upper limits is not particularly limited, but is preferably 10 degrees or more, 15 degrees or more, or 20 degrees or more. By having the angle of repose of the second pellets within the above range, the kneadability with the liquid component of the resin pellet composition and the transportability are further improved, and extrusion fluctuations can be further suppressed.

[0051] When the liquid component is extracted from the second pellets, in the case where the second pellets are porous, the porosity after the liquid component is extracted is preferably more than 10% and not more than 90%, more preferably 20% or more and not more than 80%, even more preferably 30% or more and not more than 70%, and even more preferably 40% or more and not more than 60%. When the porosity after the liquid component is extracted from the second pellets is within these ranges, the low classification property, the kneadability with the liquid component, and the transportability of the resin pellet composition tend to be further improved.

[0052] Regarding the dimensions of the second pellets, the maximum length of the second pellets is preferably 10 mm or less from the viewpoint of being less likely to clog during pneumatic transport in an empty line or the like and being easy to transport, and more preferably 6 mm or less, and even more preferably 5 mm or less, from the viewpoint of further improving transportability in an extruder. The lower limit of the maximum length is preferably 1 mm or more, more preferably 2 mm or more. The maximum length of the second pellets is preferably 1 mm or more in order to transport the resin pellet composition well, particularly in a large extruder with a large clearance between the screw and the cylinder.

[0053] The second pellets are preferably resin pellets containing polyolefin as a main component. In this specification, the term "main component" means that the second pellets contain polyolefin in a proportion of more than 50% by mass based on the total mass of all resin components of the second pellets. Examples of polyolefin include polyethylene and polypropylene, and polyethylene is preferred.

[0054] The main component of the second pellets is preferably melt-blended polyethylene. It is known in the art that the strength of a polymer molded article varies depending on the number of entanglement points between tie molecules. Without wishing to be bound by theory, it is believed that melt-blending reduces the crystallite size of the polymer and increases the number of entanglement points between tie molecules, thereby improving the strength of the resin pellets and molded articles using the same. The melt-blending of polyethylene can be carried out by a melter and / or a kneader.

[0055] The second pellets may contain polypropylene or other polyolefin resins in addition to polyethylene to improve heat resistance. In addition to polyolefins, the second pellets may contain other resins, such as polyethylene terephthalate (PET) and non-polyolefin resins such as nylon, within a range that does not impair the performance of the resin pellet composition of the present disclosure. When the second pellets are a mixture of polyethylene and a resin other than polyethylene, the proportion of the resin other than polyethylene in the pellets is preferably less than 30% by mass from the viewpoint of dispersibility and / or strength retention, more preferably less than 20% by mass, and even more preferably less than 10% by mass from the viewpoint of dispersibility. The lower limit is not particularly limited, but can be, for example, 0% by mass or more, or more than 1% by mass.

[0056] The viscosity average molecular weight (Mv) of the polyethylene contained in the second pellets or the entire resin constituting the second pellets is preferably 200,000 or more. When the Mv of the polyethylene contained in the second pellets or the entire resin constituting the second pellets is 200,000 or more, when the resin pellets are mixed with a resin containing a low molecular weight component with Mv less than 200,000 as a main component, the mechanical strength of the molded article or film of the mixture, such as tear strength and tensile strength, is significantly improved. The upper limit of the Mv is not particularly limited, but can be, for example, 5,000,000 or less, preferably 3,000,000 or less, and more preferably 2,000,000 or less.

[0057] From the viewpoint of tensile strength of the molded article, the Mv of the polyethylene contained in the second pellets is preferably more than 200,000, more preferably 300,000 or more (or more), and even more preferably 500,000 or more (or more). From the same viewpoint, the Mv of the second pellets is preferably 300,000 or more, more preferably 500,000 or more. The upper limit of the Mv is not particularly limited, but can be, for example, 5,000,000 or less, preferably 3,000,000 or less, and even more preferably 2,000,000 or less.

[0058] The polyethylene in the second pellets may be a mixture containing multiple components having different molecular weights, for example, a mixture of polyethylene with Mv 100,000 and polyethylene with Mv 700,000 may have an overall Mv of 200,000 or more.

[0059] The second pellets preferably contain less than 5% by mass of liquid components in addition to the liquid components, more preferably 2% by mass or less, and particularly preferably 1% by mass or less. The above means that the second pellets are unlikely to absorb additional liquid components in addition to the liquid components already contained therein, and the properties can be evaluated, for example, by the small change in mass before and after exposing the pellets to an excess amount of liquid components. The measurement method will be described in the Examples.

[0060] From the viewpoints of productivity, environmental consideration, etc., the second pellets are preferably made of recycled resin, and for example, as described below, it is more preferable that the second pellets are formed from a raw microporous membrane before the extraction process as a raw material for the second pellets. Even when the second pellets are made of recycled resin, the viscosity average molecular weight (Mv) of the polyethylene is preferably 200,000 or more (or more), more preferably 300,000 or more (or more), and even more preferably 500,000 or more (or more), from the viewpoint of the strength of a molded article using the resin pellets. The upper limit of the Mv is not particularly limited, but can be, for example, 5,000,000 or less, preferably 3,000,000 or less, and even more preferably 2,000,000 or less.

[0061] Examples of polyethylene include high density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMWPE), linear low density polyethylene (LLDPE), high pressure low density polyethylene, and mixtures thereof. In addition, polyethylene with a narrow molecular weight distribution obtained by utilizing a metallocene catalyst and HDPE obtained by multi-stage polymerization may be used. In this specification, ultra-high molecular weight polyethylene (UHMWPE) refers to polyethylene with a viscosity average molecular weight (Mv) of 350,000 or more.

[0062] When the second pellets contain polyethylene, the proportion of polyethylene is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total mass of the resin components of the second pellets. When the second pellets contain UHMWPE, the proportion of UHMWPE is preferably 5% by mass or more and 50% by mass or less, from the viewpoints of optical properties, strength and foreign matter removability of the molded product, and is preferably 9% by mass or more and 40% by mass or less, based on the total mass of the resin components of the second pellets, from the viewpoint of dispersibility.

[0063] The shape of the second pellets may be, for example, an oval sphere, a button shape, a polygonal shape (FIG. 4(a)(b)), a flat sphere shape (FIG. 4(c)), or the like. The second pellets may be planar, folded (folded form), separable (separable form), or laminated (laminated form). The second pellets may be small pieces obtained by cutting a sheet containing a liquid component into a polygonal shape having a maximum length of about 5 mm. The sheet containing a liquid component may be a melt-kneaded product of a resin containing polyolefin and a liquid component. Examples of the polygonal shape include a rectangle as shown in FIG. 4(a) and a triangle as shown in FIG. 4(b). The thickness of the small pieces is preferably about 0.5 mm to 3 mm. By having any one of these shapes, a resin pellet having excellent strength and optical properties when formed into a film and excellent removability of foreign matter such as fish eyes and unmelted gels can be obtained. The reason is that the pellets efficiently transmit shear force in the extruder and can be kneaded to uniformly stretch the molecular chains of the polyethylene contained in the pellets, thereby reducing foreign matter such as fish eyes and unmelted gels. The second pellets are more preferably in a folded, separable or laminated form. The reason is that in addition to reducing the foreign matter, the second pellets are more likely to retain liquid components, resulting in a resin pellet composition that is excellent in transportability, low classification properties and kneadability with liquid components.

[0064] The explanations regarding Fig. 1(a) to (d) in the "First Pellet" column also apply to the second pellet, and the explanations regarding Fig. 2(a) and (b) in the "First Pellet" column also apply to the second pellet.

[0065] The second pellets have a bulk density of 0.1 to 0.9 g / cm3 after the liquid component is extracted, as measured according to the Japan Powder Industry and Technology Association standard SAP01-79. 3 By having a bulk density in this range, a resin pellet composition can be obtained that is excellent in strength and optical properties when formed into a film, and is also excellent in the removal of foreign matter such as fish eyes and unmelted gels. The bulk density of the second pellets is preferably 0.2 to 0.8 g / cm from the viewpoint of further improving the strength, optical properties, or foreign matter removal properties of a film obtained by using the second pellets. 3 , more preferably 0.30 to 0.6 g / cm 3 , more preferably 0.4 to 0.55 g / cm 3 It is.

[0066] <Liquid components> The resin pellet composition of the present disclosure contains a liquid component in an amount of 0.1% by mass or more and 99.0% by mass or less based on the total mass of the resin pellet composition. From the viewpoints of classification, kneadability with the liquid component, and transportability, the amount of the liquid component is preferably 5% by mass or more and 80% by mass or less, 10% by mass or more and 60% by mass or less, or 20% by mass or more and 50% by mass or less. Here, the amount of the liquid component means the mass of the liquid component contained in the entire resin pellet composition, including the liquid components contained in the first pellets and the second pellets.

[0067] In the present specification, the term "liquid component" refers to a material that has fluidity at any temperature between 10°C and 100°C, preferably at room temperature of about 25°C. Examples of liquid components include lubricating oils, plasticizers, antifogging agents, and antistatic agents, and from the viewpoints of low classification, kneadability, and transportability, lubricating oils or plasticizers are preferred. Examples of plasticizers include paraffinic hydrocarbons and naphthenic hydrocarbons, and when a microporous membrane is produced by extrusion molding, paraffinic hydrocarbons are preferred, and liquid paraffin is more preferred.

[0068] <Foreign matter removability> The following criteria are used as indicators of whether the resin pellet composition can remove foreign matter such as unmelted gel (foreign matter removability): First, the resin pellet composition has a content of 5% by mass or more to 60% by mass, a melt index (MI) of 2, and a density of 0.940 g / cm 3 The polyolefin pellets are dry-blended with linear low density polyethylene (LLDPE) to prepare polyolefin pellets. The polyolefin pellets are kneaded at 200°C and 50 rpm for 10 minutes using a Toyo Seiki Co., Ltd. Labo Plastomill to obtain a molten resin. The molten resin is molded into a sheet with a thickness of 500 μm on a press plate at 10 MPa, and then stretched 5 times vertically and 5 times horizontally using a biaxial stretching machine to produce a film with a thickness of 20 μm. At this time, the 100 cm 2 of the film thus produced is 2 Preferably, there are 10 or less unmelted gels per sample, more preferably 5 or less unmelted gels, even more preferably 1 or less unmelted gel, and even more preferably 0 unmelted gels. In this case, the unmelted gel refers to a gel caused by poor dispersion of a high molecular weight component, and has a diameter of more than 0.3 mm when observed with a magnifying glass or the like. A gel having a diameter smaller than 0.3 mm or other contaminants or foreign matter is not counted as an unmelted gel.

[0069] <<Method for producing resin pellet composition>> A manufacturing method of a resin pellet composition according to the present disclosure includes, for example, a step of providing pellets (hereinafter simply referred to as "first pellet raw material") that are the raw material for the first pellets, which are porous bodies, and a liquid component, and mixing these materials to impregnate a portion of the porous body of the first pellet raw material with a portion of the liquid component.

[0070] From the viewpoint of manufacturing efficiency, the method further preferably uses recycled resin.For example, the first pellet raw material can be obtained from the microporous membrane raw material after the extraction process obtained in the process of manufacturing a polyolefin microporous membrane.The first pellet raw material obtained from the microporous membrane raw material after the extraction process does not substantially contain liquid components.Therefore, by mixing it with the liquid component, a part of the liquid component can be impregnated into a part of the porous body of the first pellet raw material, and as a result, the resin pellet composition of the present disclosure containing the first pellet can be obtained.

[0071] When the resin pellet composition of the present disclosure further contains second pellets, the production method thereof may include, for example, a method including a step of providing a first pellet raw material which is a porous body, pellets which are the raw material for the second pellets which are non-porous bodies having a resin portion containing polyolefin and a liquid component portion (hereinafter simply referred to as the "second pellet raw material"), and a liquid component, and mixing these materials to impregnate a portion of the porous body of the first pellet raw material with a portion of the liquid component.

[0072] The order of mixing is not particularly limited, and for example, (1) the first pellet raw material and the liquid component may be mixed first to impregnate a part of the porous body with a part of the liquid component, and then the second pellet raw material may be mixed; (2) the first pellet raw material not containing a liquid component may be mixed with the second pellet raw material (or with the second pellet raw material mixed in advance with a desired amount of liquid component), and a part of the liquid component contained in the second pellet raw material or attached to the surface of the second pellet raw material may be impregnated into a part of the porous body of the first pellet raw material. From the viewpoint of production efficiency, the above method (2) is preferred.

[0073] In the above method (2), it is more preferable to use recycled resin from the viewpoint of production efficiency. For example, a part of the microporous membrane raw material obtained in the process of producing a polyolefin microporous membrane can be used to produce the first pellet raw material and the second pellet raw material. More specifically, the method of producing a polyolefin microporous membrane generally includes an extrusion step of extruding a composition containing a polyolefin-containing resin and a liquid component with an extruder to form a microporous membrane raw material; and an extraction step of extracting the liquid component from the microporous membrane raw material in the presence of an extraction solvent. Here, after the extrusion step, the second pellet raw material can be obtained from the microporous membrane raw material before the extraction step, and the first pellet raw material can be obtained from the microporous membrane raw material after the extraction step. In this way, the first pellet raw material and the second pellet raw material may be obtained from a series of steps of producing a polyolefin microporous membrane, but the first pellet raw material may be obtained from one of the steps of producing separate polyolefin microporous membranes, and the second pellet raw material may be obtained from the other. That is, a composition containing a polyolefin resin and a liquid component is extruded by an extruder to form a microporous membrane raw material, and a first pellet raw material is obtained from the microporous membrane raw material obtained through a first extrusion step and an extraction step, and a second pellet raw material may be obtained from the microporous membrane raw material obtained from a second extrusion step different from the first extrusion step. The first pellet raw material obtained from the microporous membrane raw material after the extraction step does not substantially contain liquid components. Therefore, by mixing this with the second pellet raw material, a part of the liquid components contained in the second pellet raw material or attached to the surface of the second pellet raw material can be impregnated into a part of the porous body of the first pellet raw material, and as a result, the resin pellet composition of the present disclosure can be obtained.

[0074] <Method for producing microporous membrane> More specifically, the method for producing the microporous membrane is not limited, but may be, for example, a membrane produced by the method described in International Publication No. 2005 / 103127 (Patent Document 5) or International Publication No. 2006 / 38532 (Patent Document 6). For example, in this method, a plasticizer is used as a liquid component. When polyethylene with Mv of 200,000 or more is used, from the viewpoint of dispersing it, a microporous membrane can be produced by a method in which a plasticizer is mixed with the raw polyethylene and melt extruded, and the two are phase-separated when cooled in a casting device or the like, and then stretched, and the plasticizer is extracted and removed using a solvent to open holes. In the wet method, the crystals of polyethylene with Mv of 200,000 or more are swelled by the plasticizer, making it easier to disperse high molecular weight components, and a film with good membrane quality can be obtained when resin pellets are mixed with conventional LLDPE.

[0075] The porosity of the obtained microporous membrane is preferably 10% or more and 80% or less, more preferably 20% or more and 65% or less, and the air permeability is preferably 10 sec / 100 cc or more and 5000 sec / 100 cc or less, and even more preferably 50 sec / 100 cc or more and 1000 sec / 100 cc or less.

[0076] As the wet method, for example, the method described in International Publication No. 2006 / 38532 (Patent Document 6) can be mentioned. The produced microporous membrane may have a pore size of about 0.05 μm, and the resin trunk around the pores may also have a thickness of about 0.1 μm. In this case, the high molecular weight components of the polyethylene constituting the trunk are already dispersed to 0.1 μm, and when polyolefin resin pellets are produced using this microporous membrane and the produced resin pellets are melt-kneaded with general LLDPE, the dispersion of the high molecular weight components is extremely good, and a film with excellent strength and membrane quality is obtained. The thickness of the trunk can be confirmed by observation with a scanning electron microscope or the like. The strength referred to here includes tensile strength, tear strength, etc. for the film, and in this specification, the puncture strength of the film may be used as an evaluation criterion. Moreover, the membrane quality means that there are no fish eyes or unmelted gels generated on the film surface. The membrane quality may be judged by observing the number of fish eyes or unmelted gels in a film cut into a 100 mm square with a magnifying glass or by visual observation.

[0077] As a method for producing resin pellets from a microporous membrane, for example, the method described in JP 2006-21519 A (Patent Document 2) can be used. Specifically, the raw microporous membrane after the extraction step can be bundled alone, stacked in multiple layers, folded, cut, or mixed with another resin raw material, and then optionally bound by pressing, bonding, fusion, or the like, and then cut to the desired dimensions to produce the first pellet raw material. A part of the porous body may form a non-porous part by pressing, bonding, or fusion.

[0078] <Production of second pellet raw material> The second pellet raw material is produced, for example, by kneading a resin raw material such as polyethylene and a plasticizer such as a lubricant in a twin-screw extruder, cooling and solidifying the raw material extruded from a T-die in a cast device, and pulverizing or cutting the cast raw material with a pulverizer or the like. It is also produced by connecting a normal strand die to the above-mentioned extruder and cutting the produced strand with a commercially available strand cutter. The weight ratio of the resin raw material and the liquid component such as the lubricant is preferably within a range in which the second pellet of the present disclosure can be obtained, but since the liquid component bleeds from the second pellet raw material and is partially lost, it may be about 5% more than the desired amount. The second pellet raw material can also be produced by bundling the microporous membrane raw material after the extrusion process and before the extraction process alone, stacking multiple pieces, folding, cutting, or mixing with another resin raw material, and then optionally bonding it by pressing, bonding, or fusing, and then cutting it to the desired dimensions to produce the second pellet raw material.

[0079] (Mixing / Extrusion) For example, a raw material composition containing a predetermined amount of a resin raw material (polyethylene) and a liquid component (liquid paraffin) is extruded using a single extruder, and a raw material film of a microporous membrane is produced by cast molding. This raw material film is then crushed and cut to the desired size to obtain a second pellet raw material.

[0080] The method of kneading the resin composition as the raw material includes a step of kneading the raw resin and optionally a plasticizer in advance with a Henschel mixer or a tumbler mixer, and a step of feeding the kneaded mixture obtained into an extruder, and while heating and melting it in the extruder, adding a plasticizer at any ratio as necessary until a predetermined amount is reached, and further kneading. This method can obtain a sheet with good dispersion of the resin composition.

[0081] As the melt extruder, for example, a twin-screw extruder can be used. This allows a strong shear force to be applied to the resin composition, and when the raw material is a polymerized powder, the dispersibility is further improved. The L / D of the screw of the twin-screw extruder is preferably about 20 to 70, more preferably 30 to 60. Here, L represents the screw length, and D represents the screw diameter. The screw may have a full flight portion and a kneading portion such as a kneading disk or rotor. On the other hand, when the resin raw material is already processed into pellets from polymerized powder, a single-screw extruder can also be used.

[0082] In the extrusion process, the content of the plasticizer in the microporous membrane layer is selected arbitrarily, but is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. However, if the plasticizer is too much, the amount of bleeding in the casting process increases, and slippage or the like occurs between the rolls. The content of the plasticizer is preferably 90% by mass or less.

[0083] The die attached to the tip of the extruder is not particularly limited, but a T-die or the like is used. When inorganic particles or inorganic fillers are used, or when a resin composition that is easily deteriorated is used, a die that has been treated to suppress wear or adhesion due to them, such as a flow path or lip that is Teflon (registered trademark), ceramic, nickel, molybdenum, or hard chrome coated, is preferably used. A composite raw roll may be produced using a co-extrusion die.

[0084] (Casting process) The molten resin extruded from the die can be introduced into, for example, a casting device to form a raw microporous membrane (a precursor of a microporous membrane laminate). The thickness of the raw membrane is a dimension that is easy to handle as the second pellet raw material, and the maximum length is preferably 1 mm or more and 10 mm or less, more preferably 2 mm or more and 6 mm or less. The obtained sheet-like raw microporous membrane can be cut to obtain the second pellet raw material.

[0085] <Production of the first pellet raw material> The following steps for obtaining the first pellet raw material may be performed consecutively on the raw microporous membrane obtained in the above-mentioned kneading / extrusion step and casting step for producing the second pellet raw material, or may be performed on a raw microporous membrane obtained via a kneading / extrusion step and casting step different from those for producing the second pellet raw material.

[0086] (Stretching process) The raw microporous membrane obtained in the casting step is stretched (stretching step). The stretching at this time is preferably biaxial stretching, more preferably simultaneous biaxial stretching or sequential biaxial stretching. The stretching temperature is preferably within a range of 100°C to 155°C, more preferably 110°C to 140°C. From the viewpoint of membrane strength, the stretching ratio is preferably 3 times to 200 times in terms of area ratio. The stretching step may be biaxial or uniaxial stretching, and may be omitted if not necessary.

[0087] (Extraction / porosity process) The raw microporous membrane before co-stretching is immersed in an extraction solvent to extract the plasticizer (liquid component) and make it porous (extraction / porosity process), and then the membrane is thoroughly dried. When only the plasticizer is extracted, the extraction solvent is preferably a poor solvent for polyolefins and the like and a good solvent for the plasticizer, and has a boiling point lower than the melting point of the raw resin. Examples of such extraction solvents include chlorine-based solvents such as methylene chloride and 1,1,1-trichloroethane; ketones such as methyl ethyl ketone and acetone; halogen-based organic solvents such as hydrofluorocarbons, hydrofluoroethers, cyclic hydrofluorocarbons, perocarbons, and perfluoroethers; ethers such as diethyl ether and tetrahydrofuran; hydrocarbons such as n-hexane and cyclohexane; and alcohols such as methanol and isopropyl alcohol. Two or more of these extraction solvents may be used. Among the above, methylene chloride is particularly preferred. The porosity process may be performed before or after the co-stretching process. The porosity-producing step may be performed by multi-stage extraction using a plurality of extraction tanks. Examples of the extraction solvent for the inorganic filler include alkaline water. However, the inorganic filler may be left in the microporous membrane or auxiliary layer for the purpose of improving strength, or may be removed in the extraction tank.

[0088] (heat setting process) After the extraction of the plasticizer, heat setting by heating and stretching may be performed as necessary to adjust the film properties such as the film thickness and air permeability, or to prevent the film from thermally shrinking. Examples of stretching after extraction include uniaxial stretching, simultaneous biaxial stretching, sequential biaxial stretching, and transverse uniaxial stretching. The stretching temperature is preferably 100°C or higher and 155°C or lower. The stretching ratio is preferably more than 1 and 10 times or lower in area ratio. When heat treatment is performed to stabilize the dimensions of the microporous membrane, for example, a biaxial stretching machine, a uniaxial stretching machine, or both of them can be used to heat treat the microporous membrane at a temperature of 100°C or higher and 150°C or lower in order to reduce film shrinkage in a high-temperature atmosphere. Preferably, heat treatment is performed by relaxing the ratio and / or stress in the width direction, length direction, or both directions at a temperature range below the melting point of the resin constituting the raw film, the target layer, or the auxiliary layer. The heat setting temperature is more preferably from 110° C. to 140° C., and most preferably from 120° C. to 140° C. Through the above steps, a microporous membrane is produced.

[0089] (Pelletizing) The microporous membrane produced as described above is pelletized to produce the first pellet raw material. As a production method, for example, the method described in JP-A-2006-21519 (Patent Document 2) can be used. Specifically, a polyethylene raw material, for example, a polyethylene film or the above-mentioned microporous membrane, which has been produced in advance, is individually bundled, multiple layers are stacked, cut, or woven with another resin raw material (film, etc.), mixed, and then bound by pressure such as a pinch roll or an embossed pinch roll, and then cut to a desired size to produce the first pellet raw material. Each layer of the single microporous membrane constituting the first pellet raw material may have a thickness of 500 μm or less. From the viewpoints of productivity, handling, versatility, etc., it is preferable that the first pellet raw material contains two or more types of resin films having different resin compositions.

[0090] Known methods may be used, such as a method in which several layers of a film pre-wound around a paper tube or the like are stacked and compressed in the thickness direction using a roll or the like, and then cut into pieces of about 6 mm in length and width, or a method in which a film produced by the method described in JP 2006-21519 A (Patent Document 2) is compressed in the width direction using a roll while being bundled, and then cut into pieces in the length direction.

[0091] When the first pellet raw material has a fibrous component, the ultra-high molecular weight polyethylene fiber described in JP-B-6-15721 (Patent Document 7) or the fiber produced by the method described in Japanese Patent No. 4623780 (Patent Document 8) can be used. The fiber used to form the fibrous component preferably has a fiber diameter of 500 μm or less, more preferably 50 μm or less, similar to the thickness of the film.

[0092] The above-described films, microporous membranes, fibers, etc. can be used alone or in combination to form the components of the first pellet feedstock. For example, a microporous membrane containing polyethylene as a main component may be combined with a non-porous film containing polypropylene as a main component.

[0093] The first pellet raw material may contain a known antioxidant such as a phenol-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, etc. The content of the antioxidant in the first pellet raw material can be adjusted according to the application of the resin pellet composition, and is generally within the range of 100 ppm to 1 mass %.

[0094] The first pellet raw material (and the first pellets) may contain additives for modifying the first pellets, such as anti-fogging agents such as glycerin esters, slip agents such as fatty acid amides such as erucic acid, stearic acid, and oleic acid, antistatic agents, inorganic fillers such as silica and alumina, liquid paraffin, and lubricating oils, and calcium stearate as an internal lubricant.

[0095] The pellet raw material (and the first pellets) may be recycled resin pellets from the viewpoints of productivity, environmental considerations, handling properties, and the like.

[0096] FIG. 3 is a schematic diagram showing an example of a production line for the first and second pellet raw materials. In FIG. 3(a), two microporous membranes unwound from two rolls (1, 2) are bundled and pressed with an embossing roller or compression roller (3), and then cut in the MD direction with a cutter (4) included in the device to form pellets, which can be collected in a pellet container (5). In this step, it is preferable not to heat with an external heat source such as a heater. The roller (3) is preferably spot-pressed with an embossing roller. In FIG. 3(a), two microporous membranes unwound from two rolls (1, 2) are shown, but multiple regions in one microporous membrane may be joined by unwounding a component part from only one roll (1) and folding or compressing it (not shown). By adjusting the conditions of these bundling, overlapping, cutting, mixing with another resin raw material, and pressing, it is possible to obtain first and second pellet raw materials having various structures in a folded, separable, or laminated form. 3(b) is a schematic diagram showing an example of a production line for the first and second pellet raw materials having a cross-sectional shape like resin pellet (d). The microporous membrane unwound from roll (1) is rolled or folded to be bundled, and cut in the MD direction with cutter (4) into pellets to obtain resin pellets (d) in the form of a rolled or folded flat membrane.

[0097] In a conventional method for producing resin pellets, for example in the case of high density polyethylene (HDPE), resin powder polymerized in a polyethylene production plant is melt-kneaded in an extruder, and the molten resin extruded into a string shape is cut to obtain pellets with a maximum length of about 2 mm to 5 mm. In contrast, in the above method using a raw microporous membrane (film), a laminate can be obtained in which preferably a plurality of films, more preferably several hundred layers of films, are laminated.

[0098] <Mixing of first pellet raw material and second pellet raw material> The first pellet raw material and the second pellet raw material are mixed by a known blending method, such as a Henschel mixer, a tumbler mixer, or a flash mixer (Ako Corporation). The mixing ratio may be arbitrary. If the liquid component of the second pellet raw material is excessive after mixing and sticky, it is more preferable to leave it for about 1 to 60 minutes after mixing is completed, so that the first pellet raw material absorbs the excess liquid component and the stickiness disappears. By this mixing, a part of the liquid component contained in the second pellet raw material is transferred to the first pellet raw material, and a part of the porous body of the first pellet raw material is impregnated with a part of the liquid component, thereby obtaining the resin pellet composition of the present disclosure.

[0099] In the present disclosure, a method for obtaining second pellets having the preferred "mass of liquid components present on the outer surface", "mass of liquid components present inside", "angle of repose", or a combination thereof can be exemplified by removing a part of the liquid components contained in the second pellet raw material obtained in the above "production of second pellet raw material". The removal method is not particularly limited, but for example, a method of contacting the second pellet raw material with a porous material capable of absorbing the liquid components and transferring a part of the liquid components to the porous material can be exemplified. More preferably, a method of mixing the mixture of the first pellet raw material and the second pellet raw material as described above and transferring a part of the liquid components contained in the second pellet raw material to the first pellet raw material can be exemplified. This can simultaneously obtain first pellets having the preferred "mass of liquid components present on the outer surface", "mass of liquid components present inside", "angle of repose", or a combination thereof in the present disclosure. The obtained mixture of the first pellets and the second pellets may be used as the resin pellet composition of the present disclosure as it is, or may be separated into the first pellets and the second pellets and each may be used as the resin pellet composition of the present disclosure.

[0100] <<Use of resin pellet composition>> The resin pellet composition of the present disclosure can be used by itself for the production of a desired molded product. Preferably, the resin pellet composition of the present disclosure can be mixed with other materials such as other resin pellets and additives (hereinafter also referred to as "mixtures") to obtain a mixed resin composition, which can be used for the production of a desired molded product. For example, the resin pellet composition of the present disclosure can be mixed and / or added to a mixture such as pellets, powders, particles, slurries, paints, etc. containing HDPE, LDPE, LLDPE, etc. as main components by a dry mixing method or a wet mixing method to obtain a mixed resin composition, which can be used for the production of a molded product. As the dry mixing method, a method of melt mixing with a normal single-screw or twin-screw extruder, or a method described in JP-A-2006-21519 (Patent Document 2) can be used. The obtained mixed resin composition has excellent transportability, is difficult to classify, and is excellent in kneading with liquid components, so that when it is used for the production of a film, for example, a film with excellent quality in which unmelted gels that impair optical properties are reduced can be obtained. In addition, when a high molecular weight component is contained, the generation of unmelted gel during extrusion can be suppressed or eliminated despite the presence of the high molecular weight component, and the strength of the obtained film can be significantly improved. Examples of the film include a film produced by extrusion molding such as inflation molding, and a microporous film produced by a wet method, and the like, and a microporous film is preferred.

[0101] When producing a film, the mixed material is preferably LDPE or LLDPE, particularly LLDPE made from a metallocene catalyst, from the viewpoint of film strength, optical properties, or foreign matter removal. As an example, a mixed resin composition obtained by dry-blending the resin pellet composition of the present disclosure with a relatively low molecular weight polyethylene such as conventional LDPE or LLDPE has excellent transportability, low classification properties, and kneadability with liquid components. Therefore, when a film is produced using this, a film with excellent quality can be obtained with reduced unmelted gels that impair optical properties. When a high molecular weight component is contained, the strength is greatly improved while suppressing the generation of unmelted gels.

[0102] When the mixture contains LLDPE, the density of the LLDPE is preferably 900 to 945 kg / m 3 , more preferably 910 to 940 kg / m 3 , and more preferably 915 to 940 kg / m 3 The melt flow rate (MFR) of the LLDPE is preferably within a range of 0.1 to 50, more preferably within a range of 0.1 to 10, and further preferably within a range of 0.3 to 4.0.

[0103] In order to use the mixed resin composition in the production of a film to improve the strength of the film, the mixed component is preferably an LLDPE polymerized by using a metallocene catalyst and using hexene or octene as a comonomer component, and the molecular weight distribution thereof is preferably 3 or more and less than 15, more preferably 5 or more and less than 10.

[0104] The amount of the resin pellet composition of the present disclosure added to a relatively low molecular weight polyethylene such as LLDPE or LDPE is preferably 5% by mass or more and 60% by mass or less from the viewpoint of strength of a molded article and unmelted gel removal property, and more preferably 10% by mass or more and 40% by mass or less in consideration of the optical properties of the molded article. Also taking into consideration the extrudability of the mixed resin composition, it is further preferably 10% by mass or more and 30% by mass or less.

[0105] In order to improve the heat resistance of the resulting film, polypropylene can be mixed into the mixed resin composition. In this case, from the viewpoint of removing fish eyes, the viscosity average molecular weight (Mv) of the polypropylene is preferably 1,300,000 or less, more preferably 700,000 or less, and even more preferably 600,000 or less. From the viewpoint of the strength of a molded product containing polyethylene and polypropylene, the Mv of the polypropylene is preferably 100,000 or more, more preferably 200,000 or more. From the same viewpoint, it is preferable to use polypropylene whose stereoregularity has been reduced by utilizing a metallocene catalyst or the like as the mixed material, or to use a resin composition in which block polypropylene (BPP) or random polypropylene (RPP) is blended in an amount of 0.5 to 30 mass% with respect to isotactic polypropylene (IPP) as the mixed material.

[0106] In addition to the resin pellet composition of the present disclosure, the mixed resin composition may contain at least one additive selected from the group consisting of other resin components, inorganic fillers, organic fillers, antioxidants, dispersing aids, antistatic agents, processing stabilizers, crystal nucleating agents, and internal lubricants, etc. The proportion of each of these additives in the mixed resin composition is preferably 5% by mass or less, more preferably 2% by mass or less, and may be substantially 0% by mass.

[0107] Examples of the resin component include engineering plastic resins such as polyphenylene ether; polyamide resins such as nylon 6, nylon 6-12, and aramid resin; polyimide resins; polyester resins such as PET and PBT; polycarbonate resins; fluorine resins such as polyvinylidene fluoride (PVDF); copolymers of ethylene and vinyl alcohol, and C2 to C6 12the copolymer of styrene and an aliphatic monounsaturated fatty acid; a polymer of acrylic acid and / or a derivative thereof; a copolymer of styrene and a conjugated diene-based unsaturated monomer and a hydrogenated product thereof; a thermoplastic resin selected from the group consisting of a copolymer of an α-olefin and carbon monoxide and a hydrogenated product thereof; a hydrogenated product of a styrene-based polymer; a copolymer of styrene and an aliphatic monounsaturated fatty acid; a polymer of acrylic acid and / or a derivative thereof; a copolymer of styrene and a conjugated diene-based unsaturated monomer and a hydrogenated product thereof; a polyketone, etc., and further polybutene-1, polymethylpentene-1, etc. may be used.

[0108] Examples of inorganic fillers include oxide ceramics such as alumina (e.g., α-alumina), silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination.

[0109] Examples of antioxidants include phenol-based antioxidants such as "Irganox 1010", "Irganox 1076" and "BHT" (all trademarks manufactured by Ciba Specialty Chemicals), phosphorus-based or sulfur-based secondary antioxidants, and hindered amine-based weather resistance agents. These can be used alone or in combination.

[0110] From the viewpoint of strength, optical properties and foreign matter removal of the molded product obtained from the mixed resin composition, a combination of a phenol-based antioxidant and a phosphorus-based antioxidant is preferred.Specific examples include pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butylhydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butylhydroxybenzyl)benzene, tris(2,4-di-t-butylphenyl)phosphite, tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylenephosphite, 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxyphosphepine, etc.

[0111] The amount of the antioxidant is preferably 100 ppm to 10,000 ppm based on the total resin solid content of the microporous film formed using the mixed resin composition. When a phenol-based antioxidant and a phosphorus-based antioxidant are used in combination, the ratio of the phenol-based / phosphorus-based antioxidant is preferably 1 / 3 to 3 / 1.

[0112] Examples of dispersing aids for polypropylene and polyethylene include hydrogenated styrene-butadiene elastomers, elastomers obtained by copolymerizing ethylene and propylene, etc. The amount of dispersing aid is preferably 1 to 10 parts by mass per 100 parts by mass of the total amount of polypropylene and polyethylene.

[0113] Examples of the antistatic agent include amines such as alkyldiethanolamine and hydroxyalkylethanolamine; amine esters such as stearyldiethanolamine mono fatty acid ester; alkylamides such as lauric acid diethanolamide and stearic acid diethanolamide; mono fatty acid esters such as glycerin and diglycerin; anionic antistatic agents such as alkylbenzenesulfonic acid; polyoxyethylene alkyl ethers, which may be used alone or in combination. The amount of the antistatic agent is preferably 500 ppm to 10,000 ppm based on the total resin solid content of the microporous membrane formed using the mixed resin composition.

[0114] The mixed resin composition may also contain calcium stearate, magnesium stearate, or hydrates thereof, such as sodium 12-hydroxystearate, as an internal lubricant. In this case, the preferred content of the internal lubricant is in the range of 50 ppm to 5000 ppm.

[0115] The resin pellet composition of the present disclosure can be used to manufacture a molded product. For example, various moldings such as extrusion molding, injection molding, blow molding, and molding can be performed. The molded product manufactured is preferably a packaging film or an agricultural film because it has excellent optical properties, strength, and foreign matter removal properties. EXAMPLES

[0116] <Method of measuring physical properties> <Thickness of each layer and total thickness (μm)> The layer thickness was measured by cross-sectional observation using a general scanning electron microscope (S4100, manufactured by Hitachi, Ltd.).

[0117] <Viscosity average molecular weight (Mv)> Based on ASTM-D4020, the intrinsic viscosity [η] in decalin solvent at 135°C was determined. The Mv of polyethylene and polypropylene was calculated using the following formula. Polyethylene: [η] = 6.77 × 10 -4 Mv0.67 Polypropylene: [η] = 1.10 × 10 -4 Mv 0.80

[0118] <Porosity of microporous membrane (%)> The basis weight W (g / cm) was calculated from the mass of a 100 mm square microporous membrane sample. 2 ) and the average density ρ (g / cm) of the components (resin and additives) that make up the microporous membrane 3 The porosity of the microporous membrane was calculated from the thickness d (cm) of the microporous membrane using the following formula. Total layer porosity (%) = (100-W / (d×ρ))×100

[0119] <Air permeability of microporous membrane (sec / 100cc)> The air permeability of the microporous membrane was measured in accordance with JIS P-8117 using a Gurley air permeability meter "G-B2" (trademark, manufactured by Toyo Seiki Seisakusho, Ltd.) The values ​​in Table 1 are 20 μm equivalent air permeabilities calculated by proportional calculation based on the total thickness.

[0120] <Piercing strength (GF)> The puncture strength (gf) was determined by performing a puncture test using a handy compression tester "KES-G5" (manufactured by Kato Tech, trademark) under the conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / sec. The values ​​in Table 3 are puncture strengths converted to 20 μm calculated by proportional calculation based on the total thickness.

[0121] <Microporous membrane pore size (μm)> The judgment was made from surface photographs taken by surface observation using a general scanning electron microscope (S4100, manufactured by Hitachi, Ltd.).

[0122] <(Additional) Liquid Component Content (% by mass)> After measuring the mass of the first and / or second pellets, the pellets are immersed in (exposed to) an excess amount of liquid component and left at room temperature for 12 hours. Then, 10 pellets are taken out, sandwiched between tissue paper from above and below, and the liquid component on the surface is wiped off easily (for about 1 minute). After confirming that the liquid component on the surface has been removed, the mass is measured. The amount of liquid component that can be contained was calculated based on the change in mass of the pellets before and after immersion in the liquid component.

[0123] <Porosity (%) of second pellet after liquid component extraction> The porosity (%) of the second pellet after the liquid component extraction is calculated from the weight of the second pellet before and after the liquid component extraction and removal. First, 10 g of the second pellet is weighed. Next, this is immersed in an excess amount (about 1000 g) of the liquid component extraction solvent, and the liquid component is extracted and removed for the required time. For example, if the liquid component is liquid paraffin, methylene chloride can be used as the extraction solvent, and extraction should be performed for about 24 hours. The weight W1 of the pellet is then measured. If the amount of the extracted liquid component is W2, then W1 + W2 = 10 g. If the density of the liquid component of the second pellet is PL and the density of the resin component is PR, the porosity is calculated as follows. Porosity(%)=100*(W2 / PL) / (W1 / PR+W2 / PL)

[0124] <Porosity (%) of first pellet after liquid component extraction> The first pellet is impregnated with a large excess of the liquid component and left to stand at room temperature for 12 hours or more. If the pellet floats, it is pressed down with a lid or the like to sink, etc., so that the micropores of the first pellet are impregnated with the liquid component and completely replaced with air. After standing, the first pellet is taken out and the liquid component on the surface is wiped with another clean microporous membrane or tissue paper. In this way, a first pellet impregnated with the liquid component is prepared, and the porosity is calculated in the same manner as the porosity of the second pellet described above. For example, when the first pellet is composed of a microporous membrane as a constituent component, the porosity of the first pellet is generally close to the porosity of the microporous membrane, but when the microporous membrane is partially crimped, the pores of the crimped part may be blocked, and the porosity tends to be lower than the porosity of the microporous membrane.

[0125] <Bulk density of pellets after liquid component extraction (g / cm 3 )〉 After the liquid component was extracted from the pellets by the above-mentioned method, the bulk density of the pellets was measured according to the Japan Powder Process Industry and Technology Association standard SAP01-79.

[0126] <Mass of liquid component present on the outer surface of pellets> The mass of the liquid component present on the outer surface of the first and second pellets was measured by the following method. First, 20 g of pellets to be measured were collected. 20 g of pellets to be measured were wrapped in a 1 m square sheet with a thickness of 0.6 mm, which was made by stacking multiple polyethylene microporous membranes with a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm. The liquid component present on the outer surface of the pellets was wiped off by rubbing the sheet with hands from the outside. This wiping operation caused the liquid component to permeate and migrate into a part of the polyethylene microporous membrane, filling the pores of the microporous membrane, and the color of that part changed from white to translucent. This wiping operation was repeated several times by replacing the sheet until the liquid component no longer permeated the sheet, that is, until the color change of the polyethylene microporous membrane could no longer be visually confirmed. The mass of the pellets after the wiping operation was measured. The difference in mass of the pellets before and after wiping was calculated as the amount of liquid component present on the outer surface of the pellets. Note that since the difference in mass was measured before and after wiping, care was taken not to spill the pellets during the measurement, and even very small pellet particles were quantitatively collected.

[0127] <Mass of liquid components present inside the pellet> The mass of the pellet after removing the liquid component on the outer surface was measured by the same operation as that for measuring the mass of the liquid component present on the outer surface of the pellet. Then, the liquid component was extracted and removed from the pellet with a solvent, and the mass of the pellet after the liquid component extraction was measured. The solvent is not limited as long as it can extract and remove the liquid component from the pellet, but for example, when the liquid component is liquid paraffin, methylene chloride can be used as the extraction solvent. The difference in mass of the pellet before and after extraction and removal was calculated as the mass of the liquid component present inside the pellet.

[0128] <Angle of repose> The angles of repose of the first and second pellets were measured by the following method in accordance with JIS R9301-2-2:1999. That is, the method involves dropping a pellet sample onto a horizontal substrate from a funnel of a certain height, calculating the base angle from the diameter and height of the resulting cone-shaped deposit, and using this base angle as the angle of repose. The inner diameter of the nozzle of the funnel is 20 mm, and the tip of the nozzle is adjusted and fixed to a height of 200 mm from the substrate surface. 200 g of the sample is collected in a glass beaker, and the beaker is tilted while being careful not to vibrate the funnel, and 200 g of pellets are supplied from a height of about 100 mm from the upper edge of the funnel in about 60 seconds. At this time, the falling speed is kept constant. At this time, the pellets are not dropped into the center of the funnel, but are supplied in a circular motion along the circumference of the funnel wall. In this way, a cone-shaped pile of pellets (cone-shaped deposit) is formed on the substrate. The cone is observed from the side, and the angle of repose is determined as the inclination angle of the cone's slope with respect to the horizontal plane.

[0129] <Low classification (variation in bulk density)> The measurement was performed by the following method according to JIS-Z2504. 20 kg of the resin pellet composition was charged into a raw material hopper having a truncated cone shape with a height of 600 mm, a diameter of 400 mm at the top, and a diameter of 250 mm at the bottom, a hemispherical dome at the bottom, and an opening for extracting the raw material from the bottom end of the dome. Immediately after charging, the resin was extracted five times from the top surface of the raw material with a 200 cc cup, and the first bulk density was calculated from the average weight. Next, 15 kg of the raw material was extracted from the opening at the bottom of the hopper, and the second bulk density was then calculated in the same manner. At this time, the bulk density variation was determined by the ratio of the bulk densities (first bulk density / second bulk density). Evaluation was performed as follows, with A being considered as passing. A The bulk density ratio is in the range of 0.95 or more and 1.05 or less. B The bulk density ratio is less than 0.95 or more than 1.05. D Film formation is not possible.

[0130] <Piping transportability> 5 kg of the resin raw material composition for microporous membrane to be measured was prepared and transported to a height of 2 m using an air transport autoloader connected to a 5 m long polyvinyl chloride hose. As in the above-mentioned method for measuring low fractionation, the ratio of bulk density before and after transport (before transport / after transport) was measured. A was deemed to be acceptable. A The bulk density ratio is in the range of 0.95 or more and 1.05 or less. B The bulk density ratio is less than 0.95 or more than 1.05. D Film formation is not possible.

[0131] <Extrusion Fluctuation> During the extrusion process, the resin pressure fluctuation at the extruder outlet was measured for one minute, and the maximum and minimum differential pressure (△P) was measured. A or B was deemed acceptable. A △P is less than 0.5 MPA. B △P is 0.5 MPA or more and less than 1 MPA. D △P is 1 MPA or more, or film formation is not possible.

[0132] <Unmelted gel> The following criteria are used as indicators of whether the resin pellet composition removes foreign matter such as unmelted gel (unmelted gel or undispersed gel). First, liquid paraffin is added to the resin pellet composition. The amount of liquid paraffin after addition, including the amount already contained in the resin pellet composition, was 65% by mass. This was kneaded at 160°C and 50 rpm for 2 minutes to obtain a molten resin. The obtained molten resin was molded into a sheet with a thickness of 500 μm on a press plate at 10 MPa, and then stretched vertically 5 times and horizontally 5 times using a biaxial stretching machine to produce a film with a thickness of 20 μm. At this time, 100 cm of the film thus produced was 2 The evaluation was based on the number of unmelted gels present per unit area and was based on the following criteria. A: There are 0 unmelted gels. B: 1 to 5 unmelted gels are present. D: Six or more unmelted gels are present, or film formation is not possible. In this case, unmelted gel is caused by poor dispersion of high molecular weight components and refers to a particle with a diameter of more than 0.3 mm when observed with a magnifying glass, etc. A particle with a diameter smaller than 0.3 mm or other contaminants or foreign matter is not counted as an unmelted gel.

[0133] <Production Example of Resin Pellet Composition> Example 1 (1) Production of secondary pellet raw materials The second pellet raw material was produced using a microporous membrane mainly containing high molecular weight polyethylene as a constituent part, as follows. First, 90% by mass of powder-like polyethylene (HDPE1) with a viscosity average molecular weight of 400,000 and 10% by mass of polypropylene (PP1) with a viscosity average molecular weight of 700,000 were used as raw material resins, and 0.3 parts by mass of tetrakis-[methylene-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane as an antioxidant was mixed with 100 parts by mass of the raw material resin. These raw materials were stirred in a Henschel mixer to prepare the raw material.

[0134] Next, this raw material was fed into a twin-screw extruder (diameter 41 mm, L / D=49). In the middle of the cylinder of the extruder, 200 parts by mass of liquid paraffin (LQ1, kinematic viscosity at 38°C: 75.9 cSt, density: 868 kg / m 3 ) was injected. A 150 mesh screen and a metering gear pump were placed between the extruder and the die. The die and extruder were set at 200°C. A T-die was used as the die. The molten film raw material coming out of the die was cooled and solidified by a cast roll to form a cast raw material sheet with a thickness of 0.8 mm. This cast raw material sheet was crushed at room temperature in a sheet crusher to obtain a pellet raw material with a maximum length of 5 mm. This was used as the second pellet raw material.

[0135] The surface of the second pellet material thus obtained was sticky due to the excess liquid component that had bled out, and the pellets stuck together, making it impossible to transport them through piping using air or the like.

[0136] (2) Manufacturing the first pellet raw material The cast raw sheet was stretched to an area ratio of 100 at 120°C using a biaxial stretching machine, immersed in methylene chloride to extract and remove liquid paraffin, and then dried. Further, heat treatment was performed in a heating furnace at 130°C to obtain a microporous membrane with a thickness of approximately 6 μm. During the production of this microporous membrane, extrusion fluctuation occurred, and a large amount of undispersed gel remained. This is presumably due to classification of the powder and pellet portions in the raw material.

[0137] The microporous membrane was slit to a width of 350 mm and wound on a paper tube. The length of the microporous membrane was 300 m. A small amount of unmelted gel was observed in the microporous membrane. The average pore size of the microporous membrane was 0.05 μm, and the pores were uniformly open over the entire surface.

[0138] This microporous membrane was rolled into a long string in the MD, which was then compressed with an embossed pinch roll and cut with a commercially available strand cutter to obtain a white first pellet raw material in the form of a micro-sheet with a maximum length of 6 mm.

[0139] When a grain of the first pellet raw material was taken in the hand and kneaded with the hands, some of it separated and the original microporous membrane could be extracted, but many of the grains remained bound together. Some of the particulate components were broken down into multiple parts, but many grains did not break down into multiple parts. When liquid paraffin was dropped onto the first pellet raw material, most of the first pellet raw material changed from white to translucent. This suggested that some of the liquid paraffin was absorbed into the first pellet raw material.

[0140] (3) Mixing the first pellet raw material with the second pellet raw material A total of 10 kg of the first pellet raw material (50% by mass) and the second pellet raw material containing liquid paraffin (including 35% by mass of the resin component of the second pellet raw material and 65% by mass of liquid paraffin) were weighed and put into an 80-liter tumbler mixer. The mixture was stirred at 30 rpm for 5 minutes and allowed to stand for 30 minutes. In this manner, the resin pellet composition of the present disclosure was obtained. That is, this mixture contains 32.5% by mass of liquid paraffin as a whole. Tables 2 and 3 show the contents of the first pellets and the second pellets in the resin pellet composition (R) obtained after standing for 30 minutes, and the amount of liquid paraffin contained in each of them. The first pellets are impregnated with a portion of the liquid paraffin contained in the second pellets.

[0141] (4) Production of microporous membrane for evaluation The resin pellet composition obtained by the above methods (1) to (3) was used as a raw resin, and liquid paraffin was added to the extruder so that the total amount was 70 mass %, and a cast raw sheet was obtained by the same method as the above method (1). The obtained cast raw sheet was stretched to an area ratio of 45 times under conditions of 120°C in a biaxial stretching machine, immersed in methylene chloride to extract and remove the liquid paraffin, and then dried. Further, it was heat-treated under conditions of 130°C in a heating furnace, and a microporous membrane with a thickness of 6 μm was obtained. This microporous membrane was slit into a width of 30 cm and wound on a paper tube. The length of the microporous membrane was 300 m.

[0142] The microporous membrane produced from the resin pellet composition in Example 1 had good performance in terms of low classification, unmelted gel, extrusion fluctuation, and piping transportability. The physical properties of this microporous membrane were that the surface condition was extremely good, and no unmelted gel of high molecular weight components was observed. Therefore, the strength was also high. The average pore size of this microporous membrane was 0.05 μm, and the pores were uniformly open over the entire surface. In addition, the first pellet taken out from the resin pellet composition could further contain 1% by mass or more of a liquid component based on its mass.

[0143] Examples 2 to 7, 9 and 10 The production conditions and compositions were changed as shown in Table 2, and resin pellet compositions were produced in the same manner as in (1) to (3) of Example 1, and microporous membranes were produced in the same manner as in (4). All evaluation results were good. Furthermore, the first pellets taken out of the resin pellet composition were able to further contain 1% by mass or more of a liquid component based on the mass of the first pellets.

[0144] Example 8 The first pellet raw material and the second pellet raw material were produced in the same manner as in (1) and (2) of Example 1. Next, in (3) of Example 1, in addition to the first pellet raw material and the second pellet raw material, another resin raw material (C) was mixed to produce a resin pellet composition. Then, a microporous membrane was produced in the same manner as in (4). All of the evaluation results were good. In addition, the first pellets taken out from the resin pellet composition could further contain 1% by mass or more of a liquid component based on the mass of the first pellets.

[0145] < Comparative Example 11〉 In Example 1, the second pellets were taken out from the resin pellet composition 30 minutes or more after the first pellet raw material and the second pellet raw material were mixed. Comparative Example 11 The results of the evaluation were all good.

[0146] < Comparative Example 12〉 The first pellets were taken out from the resin pellet composition 30 minutes or more after the first pellet raw material and the second pellet raw material were mixed in Example 1. Only the first pellets were taken out. Comparative Example 12 The results of the evaluation were all good.

[0147] Comparative Example 1 Using only the second pellet raw material of Example 1 without mixing it with the first pellet raw material, an attempt was made to produce a microporous membrane by the above methods (1) to (4). The second pellet raw material had a sticky liquid component on the surface and could not be transported through piping, and adhered to the inside of the hopper of the extruder, making it impossible to feed a fixed amount to the extruder. Melt fracture and unmelted gel occurred, and membrane production was not possible.

[0148] Comparative Example 2 Only the first pellet raw material of Example 1 was used without mixing with the second pellet raw material, and a microporous membrane was produced by the above methods (1) to (4). The extrusion fluctuation was unacceptable, and the unmelted gel was also unacceptable. Both of these results suggest that the dispersion in the extruder was not very good. This is presumably due to the influence of the pores contained in the first pellet raw material.

[0149] Comparative Example 3 Microporous membrane production was attempted using the above methods (1) to (4) with the composition shown in Table 3. The second pellet raw material had a sticky liquid surface and could not be transported through piping, and adhered to the inside of the extruder hopper and the like, making it impossible to feed a fixed amount to the extruder. Melt fracture and unmelted gel occurred, and membrane production was not possible.

[0150] Comparative Example 4 A microporous membrane was produced by the above methods (1) to (4) using the composition shown in Table 3. There was a large amount of unmelted gel, and the membrane was unacceptable.

[0151] Comparative Example 5 A microporous membrane was produced using pelletized high density polyethylene (HDPE3) and polypropylene pellets (PP1) in the same manner as in (1) to (4) above. There was a large amount of unmelted gel, and the membrane was unacceptable.

[0152] <Reference example> A microporous membrane was produced using powdered high density polyethylene (HDPE1) and polypropylene pellets (PP1) in the same manner as in (1) to (4) above. This is the same as the microporous membrane shown in the first pellet raw material production method in Example 1. Due to classification of pellets and powder, the extruder configuration used in this example contained a very large amount of unmelted gel, and was unacceptable as a product.

[0153] [Table 1]

[0154] [Table 2]

[0155] [Table 3]

[0156] [Table 4]

[0157] [Table 5] [Industrial Applicability]

[0158] The resin pellet composition of the present disclosure can be used for molding and processing a microporous membrane, etc. In addition, the resin pellet composition of the present disclosure can be mixed with a material to be mixed, such as other resin pellets, to obtain a mixed resin composition, which can be used for molding and processing a microporous membrane, etc. [Explanation of symbols]

[0159] 1 component 1 2 Component 2 3. Embossing roller or compression roller 4 cutters (included inside) 5 Pellet container

Claims

1. A resin pellet composition comprising first pellets containing a polyolefin and second pellets containing a polyolefin, the first pellet is a porous body, and a part of the porous body is impregnated with a plasticizer; the second pellet is a non-porous body having a portion made of the resin containing the polyolefin and a portion made of the plasticizer, the first pellet has a porosity of 20% or more and 60% or less after the plasticizer is extracted from the first pellet; the mass of the plasticizer present on the outer surface of the first pellet is 10 mass% or less with respect to the total mass of the first pellet; the mass of the plasticizer present inside the first pellet is 0.5 mass % or more and 30 mass % or less with respect to the total mass of the first pellet; the mass of the plasticizer present on the outer surface of the second pellet is 10 mass% or less with respect to the total mass of the second pellet; the mass of the plasticizer present inside the second pellet is 30% by mass or more and 70% by mass or less with respect to the total mass of the second pellet; the amount of the plasticizer contained in the resin pellet composition is 5% by mass or more and 60% by mass or less based on the total mass of the resin pellet composition, A resin pellet composition, wherein the mass of the plasticizer present on the outer surface is measured by the method (1) below, and the mass of the plasticizer present inside is measured by the method (2) below. (1) 20 g of the first pellets or the second pellets are taken and wrapped in a square sheet having sides of 1 m and a thickness of 0.6 mm, the sheet being made of multiple laminated polyethylene microporous membranes having a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the plasticizer present on the outer surface of the pellets is wiped off. When the plasticizer migrates to the sheet, the color of that portion changes to translucent. The sheet is replaced and the wiping operation is repeated several times until no color change is observed in the sheet. Then, the mass of the pellet is measured, and the difference in mass before and after the wiping operation is regarded as the amount of the plasticizer present on the outer surface of the first pellet or the second pellet. (2) 20 g of the first pellets or the second pellets are taken and wrapped in a square sheet having sides of 1 m and a thickness of 0.6 mm, the sheet being made of multiple laminated polyethylene microporous membranes having a porosity of 38%, a puncture strength of 280 gf, a pore size of 0.06 μm, and a thickness of 6 μm, and the plasticizer present on the outer surface of the pellets is wiped off. When the plasticizer migrates to the sheet, the color of that portion changes to translucent. The sheet is replaced and the wiping operation is repeated several times until no color change is observed on the sheet. After that, the plasticizer is extracted and removed from the pellets with a solvent, and the difference in mass between before and after the extraction is taken as the mass of the plasticizer present inside the first pellets or the second pellets.

2. A resin pellet composition as described in claim 1, wherein the porous body of the first pellet has a microporous membrane-like component and / or a bundle, knitted fabric, woven fabric or nonwoven fabric-like component made of fibers or hollow yarns.

3. The porous body of the first pellet includes a microporous membrane-like component having a thickness of 50 μm or less and a component having fibrils having a diameter of 1 μm or less, and / or The resin pellet composition according to claim 2, wherein the porous body of the first pellet includes a component part in the form of a bundle, knit, woven fabric or nonwoven fabric made of fibers or hollow fibers, the component part having a fiber diameter of 500 μm or less.

4. A resin pellet composition described in any one of claims 1 to 3, wherein the amount of the plasticizer contained in the first pellet is 0.1 mass% or more and 30 mass% or less, based on the total mass of the resin pellet composition.

5. The viscosity average molecular weight of the polyolefin contained in the first pellets or the viscosity average molecular weight of the entire resin constituting the first pellets is 200,000 or more; The resin pellet composition according to any one of claims 1 to 4, wherein the first pellet is in a folded, separable, or stacked form.

6. A resin pellet composition described in any one of claims 1 to 5, wherein the first pellets may contain, in addition to the plasticizer, 5% by mass or more of a further plasticizer.

7. The resin pellet composition according to any one of claims 1 to 6, wherein the mass ratio of the first pellets to the second pellets (first pellets / second pellets) is 10 / 90 to 90 / 10.

8. The resin pellet composition according to any one of claims 1 to 7, wherein the first pellets and / or the second pellets contain polyethylene having a viscosity average molecular weight of 200,000 or more.

9. The resin pellet composition according to any one of claims 1 to 8, wherein the first pellets and / or the second pellets are made of recycled resin.

10. The amount of the plasticizer contained in the second pellets is 20 mass% or more based on the total mass of the resin pellet composition.

11. The resin pellet composition according to any one of claims 1 to 10, wherein the first pellets and / or the second pellets have an angle of repose of less than 60 degrees.

12. A method for producing a microporous polyolefin membrane, comprising extruding and stretching the resin pellet composition according to any one of claims 1 to 11, and extracting the plasticizer with a solvent to open pores.

13. A method for producing a resin pellet composition according to any one of claims 1 to 11, comprising the steps of: an extrusion step of extruding a composition containing a polyolefin-containing resin and a plasticizer with an extruder to form a raw microporous membrane; an extraction step of extracting the plasticizer from the raw microporous membrane in the presence of an extraction solvent; Including, The method for producing a resin pellet composition further includes, after the extrusion step, obtaining a second pellet raw material from the microporous membrane raw material before the extraction step, obtaining a first pellet raw material from the microporous membrane raw material after the extraction step, and mixing the first pellet raw material and the second pellet raw material.

14. A method for producing a resin pellet composition according to any one of claims 1 to 11, comprising the steps of: a first pellet raw material production step including a first extrusion step of extruding a composition containing a polyolefin-containing resin and a plasticizer with an extruder to form a raw microporous membrane; an extraction step of extracting the plasticizer from the raw microporous membrane obtained in the first extrusion step in the presence of an extraction solvent; and obtaining a first pellet raw material from the raw microporous membrane after the extraction step; A second extrusion step of extruding a composition containing a polyolefin-containing resin and a plasticizer with an extruder to form a raw microporous membrane, and a second pellet raw material production step of obtaining a second pellet raw material from the raw microporous membrane obtained in the second extrusion step; and A step of mixing the first pellet raw material and the second pellet raw material. The present invention further provides a method for producing a resin pellet composition.

Citation Information

Patent Citations

  • Preparation process of porous polypropylene microparticle

    CN100999597A

  • Flat blow molding device

    JP1994015721A

  • Improved polyethylene composition

    JP1998101854A

  • String, pellet, manufacturing method of string and pellet and manufacturing apparatus of these

    JP2006021519A

  • Ultra-high-molecular-weight polyethylene particulate excellent in heat resistance and method for producing the same

    JP2007023171A